PENGARUH PERILAKU KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - Furqon, Mohammad Amir; Rizal, Zef (JURNAL AKUNTANSI DAN INVESTASI, 2019)
The main problem in this study is whether leadership behavior based on structural initiatives and leadership behavior based on attention to subordinates influences the performance of employees. Bunga Baby Shop in Sampang Regency. Among leadership behaviors based on structural initiatives and leadership behavior based on the attention of which subordinates are the most dominant influence on the performance of employees. Bunga Baby Shop in Sampang Regency. From the research, valid and reliable data has been obtained so that it can be continued with the following analysis, namely the multiple linear regression analysis technique as well as the T test and F test with the help of SPSS.The results of this study indicate that through simultaneous testing (F test), the independent variable of leadership behavior (X) simultaneously has a significant effect on employee performance dependent variables (Y). This is evidenced by the calculated F value of 73,323 greater than the F table of 3.44. Furthermore, from the results of statistical tests it is known that partially the independent variable (X) consisting of structural initiatives and attention to subordinates as a whole has an effect on employee performance at Bunga Baby Shop in Sampang Regency. And the variable attention to subordinates is the most dominant variable influence on the performance of employees of Bunga Baby Shop in Sampang Regency. Therefore, it is expected that Bunga Baby Shop in Sampang Regency will maintain and increase attention to subordinates to this variable by increasing the attention of employees.